2020
DOI: 10.1182/bloodadvances.2019000084
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gender and caregiving responsibilities on academic success in hematology

Abstract: We previously identified gender disparities in academic success during evaluation of the American Society of Hematology (ASH) Clinical Research Training Institute (CRTI) and hypothesized that it may be related to caregiving. The objective was to evaluate the impact of gender and caregiving responsibilities on academic success. A cross-sectional survey that included a question about caregiving responsibilities was distributed to alumni who participated in CRTI from 2003 to 2016 and asked about academic producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
0
10
1
Order By: Relevance
“…With the additional pressures of COVID‐19, many female physicians have found the elusive work–life integration even less tenable. Panelists stated, and prior literature supports, the notion that women disproportionately hold the greater burden of household responsibilities, including homeschooling, childcare, meal preparation, cleaning, and caring for elderly family members 11–13 . One panelist noted that the myth of the work–life “balance” had only been exacerbated by the pandemic, and the additional household responsibilities and tasks took time away from academic pursuits, leaving less, and more fragmented, time for research and scholarly activities.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the additional pressures of COVID‐19, many female physicians have found the elusive work–life integration even less tenable. Panelists stated, and prior literature supports, the notion that women disproportionately hold the greater burden of household responsibilities, including homeschooling, childcare, meal preparation, cleaning, and caring for elderly family members 11–13 . One panelist noted that the myth of the work–life “balance” had only been exacerbated by the pandemic, and the additional household responsibilities and tasks took time away from academic pursuits, leaving less, and more fragmented, time for research and scholarly activities.…”
Section: Methodsmentioning
confidence: 99%
“…Pregnancy and maternity leave, a uniquely female experience, often slow down professional clocks and advancement. Prior studies have suggested that these additional responsibilities are directly responsible for the fewer publications, less institutional support, delayed career progression, and lower career satisfaction of women academicians 11–13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, parenting responsibilities have been correlated with ongoing disparate professional development and salary between men and women. 13–17 Physician mothers are more likely to turn down leadership and scholarship opportunities because of parenting responsibilities, yet are less likely to feel comfortable discussing parenting challenges with their leadership. 18 It is also prescient to note that disruptions from the COVID-19 pandemic have led to unprecedented increases in challenges and stress for physician parents.…”
Section: Introductionmentioning
confidence: 99%
“…3 In a follow-up evaluation, we found that the gender disparity persisted and was not explained by caregiving responsibilities. 4 Demographic characteristics such as gender, race, and ethnicity are variables previously associated with academic success. These fixed variables are not modified by training experiences.…”
Section: Introductionmentioning
confidence: 99%